Pengaruh Metode Pembelajaran dan Kemandirian Belajar Terhadap Hasil Belajar Sejarah Siswa di SMAN 7 Cirebon - Nita Agustinawati (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2014)
Abstract The aim of the study is to reveal the impact of instructional method and learning autonomy on the outcome of history learning students. This research is conducted in SMAN 7 Cirebon academic year 2013/2014. The result of the research: (1) From the history learning outcome of students who used instructional method of Think Pair Share were higher than those who used learning conventional method; (2) There were interactions between instructional method and learning autonomy on history learning outcome; (3) The History learning outcome of students were taught by Think Pair Share and who has higher and learning autonomy level has higher than were taught by conventional method; (4) The history learning outcome of students were taught by Think Pair Share and who has lower learning autonomy level has lower than were taught by conventional method. Keywords : history learning outcome, instructional method, learning autonomy